Diglosia dan Bilingualisme Sebagai Fenomena Berbahasa Dalam Bahasa Tutur Yang Digunakan Mahasiswa di Lingkungan Kampus - Rifky Afriazi; Amalia Fauziah; Ichsan Fauzi Rachman (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research aims to describe the language used by students in the campus environment, both the spoken language used by students outside of learning hours and the spoken language used when students present in front of their class. The sample for this research was all class A students of the Indonesian Language Education Department, Semester IV, Siliwangi University. The research method used is descriptive qualitative. Where researchers carry out studies first, so that they can provide relevant images. This research uses three stages, namely data collection, data analysis, and data presentation. Data collection was carried out by observing students who were chatting with their friends during break time, and comparing it with the spoken language used by students when they were presenting. Then researchers can analyze this phenomenon by finding out the factors that cause diglossia, the characteristics of diglossia situations, and the influence of diglossia on learning. In this study, researchers can describe the results of the discussion regarding the influence of diglossia on education, whether it has a positive effect or a negative effect.